2021
DOI: 10.3390/app11020724
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Efficacy of Contact Lens Drug-Delivery Systems in Glaucoma Management. A Systematic Review

Abstract: Adherence is crucial in medical glaucoma therapy, although half of the patients skip eyedrops. In recent years alternative drug-delivery systems have been developed. One of the most promising seems the contact lens (CL). This systematic review aims to present the in vivo efficacy of different CL drug-delivery systems. A total of 126 studies were identified following a literature search adhering to the preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines. After full-text evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 81 publications
(160 reference statements)
0
4
0
Order By: Relevance
“…Moreover, alternative delivery systems for IOP lowering medications, which do not require the daily eye drops administration, will permit the reduction of the cumulative burden of the medical therapy on the ocular surface. Based on this need, slow-release devices designed to be introduced in the lacrimal punctum, or into the fornix, the subconjunctival space, or inside the anterior chamber are being developed (Figus et al 2020;Sartini et al 2021).…”
Section: Major Gaps In Knowledge and Possible Solutionsmentioning
confidence: 99%
“…Moreover, alternative delivery systems for IOP lowering medications, which do not require the daily eye drops administration, will permit the reduction of the cumulative burden of the medical therapy on the ocular surface. Based on this need, slow-release devices designed to be introduced in the lacrimal punctum, or into the fornix, the subconjunctival space, or inside the anterior chamber are being developed (Figus et al 2020;Sartini et al 2021).…”
Section: Major Gaps In Knowledge and Possible Solutionsmentioning
confidence: 99%
“…The use of polymer-based self-assembled drug delivery systems allows for the effective and long-term delivery of one or more drugs to treat glaucoma [31]. Herein we focus on polymer-based self-assembled drug delivery systems, especially non-surgical and nonimplanted systems positioned on or near the ocular surface, including Eye drops [32,33], Hydrogels [34,35], and Contact lenses [36,37], all incorporating polymers. These drugencapsulating systems function as effective drug delivery mechanisms, ensuring sustained drug release.…”
Section: Polymer-based Delivery Systems For Glaucoma Treatmentmentioning
confidence: 99%
“…[35] Functional nanoparticles with unique properties, such as no/low cytotoxicity, excellent physical/chemical features, and drug-delivery ability, have also been employed to improve/integrate some SCL properties. [51,62,[88][89][90] For example, it has been reported that the nanoparticles were incorporated into CL polymers and gelling systems to enhance mechanical strength and elasticity of CLs. [34] For example, organic dyeencapsulated silica nanoparticles were applied with PHEMA or PDMS to obtain precise biosensing capability, with the detection sensitivity of 0.5-5 mM of blood glucose.…”
Section: Encapsulationmentioning
confidence: 99%